PENGARUH PENGALAMAN DENGAN BULLYING TERHADAP KEPERCAYAAN DIRI SISWA MTs MIFTAHUL ULUM MUKTIJAYA KECAMATAN MUARA TELANG KABUPATEN BANYUASIN - Siti Rahmah; Nyayu Khodijah; Abu Mansur (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2021)
Acts of violence in schools are increasingly prevalent with a lot of reporting about acts of violence both in print and in electronic media. One example of acts of violence that occur at school is bullying, victims of bullying have poor social adjustments that result in students withdrawing from relationships, becoming moody, and even lazy to go to school. So that it affects the confidence of students who experience bullying. The purpose of this research is to find out how the experience of bullying and to know how the students ' self-confidence and how the experience bullying influences the students' self-confidence in MTs Miftahul Ulum Muktijaya Muara Telang District, Banyuasin Regency.This research belongs to the type of quantitative research with data analysis techniques using Product Moment correlation. Sampling using saturated sampling techniques with a population of 65 students. And data collection techniques using the method of observation, questionnaires, and documentation. The results of this study were obtained: 1) experience with bullying experienced by students of MTs Miftahul Ulum Muktijaya Muara Telang District Banyuasin Regency classified in the high category with a percentage of 38% with a total of 25 students 2) student confidence MTs Miftahul Ulum Muktijaya Muara Telang District Banyuasin Regency is classified in the medium category with a percentage of 68% with a total of 44 students 3) There is an influence of experience with bullying on student confidence in Ms. the value of t count is greater than the value of t table with a significant level of 5% or a significant level of 1% that is 0.2058 <2.19> 0.2441 then Ho is rejected, meaning that there is a significant influence between experience with bullying on student confidence in MTs Miftahul Ulum Muktijaya Muara Telan District g Regency of Banyuasin.